Atypical Chronic Inflammatory Demyelinating Polyneuropathy With Relapsing Sensory-Predominant Sensorimotor Neuropathy - Yee Wen Yong; Bryan Setyoputra; Annisa Kusuma Dewi; Anyeliria Sutanto (Universitas Pelita Harapan, 2025)
Introduction: Chronic inflammatory demyelinating polyneuropathy (CIDP) is a rare, acquired autoimmune neuropathy with progressive symptoms. Intravenous immunoglobulin (IVIg) and corticosteroids are effective first-line therapies; however, many patients experience residual symptoms or relapse within the first year.Case Presentation: A 39-year-old male with an initial diagnosis of carpal tunnel syndrome presented with a 13-month history of progressive sensory disturbances, evolving from lower limb paresthesia with gait instability. EMG confirmed demyelinating and axonal sensorimotor polyneuropathy consistent with CIDP. He was hospitalized and responded well to intravenous methylprednisolone and IVIg, but relapsed nine months later after a respiratory infection, presenting with distal sensory symptoms and preserved strength. Cerebrospinal fluid analysis showed albuminocytologic dissociation, while autoimmune nodopathy markers were negative. Retreatment with IVIg and methylprednisolone led to clinical improvement, with only mild exertion-related symptoms at two-month follow-up.Discussion: This case highlights a rare sensory-predominant variant of CIDP with relapse triggered by infection. Relapses often require renewed immunotherapy, with corticosteroids and IVIg as first-line treatments; long-term management may include maintenance IVIg and gradual steroid tapering.Conclusions: Early recognition, appropriate immunotherapy, and long-term monitoring are essential to sustain remission and prevent disability in sensorypredominant CIDP.Keywords: Chronic inflammatory demyelinating polyneuropathy; electrodiagnostic studies; immunotherapy; relapse; sensory-predominant